Pengaruh Servicescape Dan Kualitas Layanan Terhadap Kepuasan Konsumen Pada Rumah Makan Tepian Pandan Di Tenggarong - Fahleti, Widya Hana (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2018)
Abstract:Customer satisfaction has become a very important issue, and many companies invest resources on consumers and continually strive to find information on how to improve customer satisfaction. One way to do manager in defending consumers and attract new customers by using servicescape theory and coupled with quality service Employers use the service environment as a way to demonstrate the qualities of its business, with the aim to make customers feel satisfied with the quality and service provided to consumers. The object of this research was conducted at the edges Spot Pandan Tenggarong. This study aims to identify and analyze the influence servicescape influence on consumer satisfaction and quality of service for customer satisfaction at Rumah Makan Tepian Pandan TenggarongÂ  Sample research data amounted to 80 people were taken randomly with traffic levels more than once. Data were analyzed with the help of SmartPLS application to determine the relationship of each partial latent variables. The findings indicate that the hypothesis is rejected servicescape no significant effect on customer satisfaction, and the second hypothesis is accepted, the quality of service significantly influence customer satisfactionKeywords : servicescape, service quality and customer satisfaction